Expression of Group IIA Secretory Phospholipase A2 Is Elevated in Prostatic Intraepithelial Neoplasia and Adenocarcinoma - Jiang, Jiazhong (American Society for Investigative Pathology, 2002)
Phospholipase A2 (PLA2) enzymes release arachidonic acid from cellular phospholipids in a variety of mammalian tissues, including prostate. Group IIa secretory PLA2 (sPLA2) can generate arachidonate from cellular phospholipids. We examined the group IIa sPLA2 expression in benign prostatic tissues, prostatic intraepithelial neoplasia (PIN), and adenocarcinoma to determine whether sPLA2 expression is altered in the carcinogenesis of human prostatic cancer. Thirty-three of 74 total cases (45%) of benign prostatic tissue showed positive immunohistochemical staining for group IIA sPLA2, whereas 63 of 69 total cases (91%) of high-grade PINs and 70 of 78 total cases (90%) of adenocarcinomas gave positive results. Four of 10 cases of low-grade PIN showed positive immunoreactivity for sPLA2. The number of cells staining for sPLA2 was significantly less in benign epithelium (4%) and low-grade PIN (4%) compared to high-grade PIN (40%) or adenocarcinoma (38%) (P < 0.001). There was no significant difference between high-grade PIN and adenocarcinoma in the number of cells staining positively for sPLA2. The intensity of sPLA2 immunoreactivity was also different among benign prostatic tissue, low-grade PIN, high-grade PIN, and prostatic adenocarcinoma specimens. The malignant cells demonstrated more intense immunohistochemical staining (moderate to strong staining in 81% and 69% cases for high-grade PIN and adenocarcinoma, respectively) than benign glands (moderate staining in 11% of cases). No strong staining was observed in benign glands or low-grade PIN. Our data are consistent with the contention that group IIA sPLA2 expression is elevated in neoplastic prostatic tissue and support the hypothesis that dysregulation of sPLA2 may play a role in prostatic carcinogenesis.